PENGARUH BRAND IMAGE DAN WORD OF MOUTH TERHADAP KEPUTUSAN WISATAWAN DENGAN HARGA SEBAGAI MEDIASI DI THE ROYAL PITA MAHA - Negara, I Gde Putu Tangkas Tatwa; Agustini, Ni Luh Putu; Marbun, Saortua (Universitas Tabanan, 2025)
This study aims to analyze brand image,Word of Mouth (WOM), price on tourist decisions at The Royal Pita Maha. This research was conducted at The Royal Pita Maha. The research design used in this study was quantitative., The respondents for this study were all consumers at The Royal Pita Maha. The sample was drawn by multiplying the number of items in the questionnaire by 5 to 10.purposive samplingThis study used a sample size of 18 years old and above, who had stayed at The Royal Pita Maha and were willing to complete a questionnaire. Data collection methods included questionnaires and interviews. And documentation. The analysis technique in this study uses PLS analysis.. The results of the analysis show that 1)Brand imagehas a positive and significant influence on tourist decisions. The test results show the value of the influencebrand imagehas a positive and significant effect on tourist decisions, 2) Word of Mouth (WOMhas no significant effect on tourist decisions, 3) Price has a positive and significant effect on tourist decisions, 4)Brand imagehas a positive and significant effect on prices, 5)Word of Mouth(WOM) has a positive and significant influence on, 6) Brand Imagehas a positive and significant influence on tourist decisions through price, 7)Word of Mouth (WOM)has a positive and significant influence on tourist decisions through price. Suggestions in this study The Royal Pita Maha will increase the uniqueness ofbrandowned so that the difference is visible withcompetitor dan word of mouthThe Royal Pita Maha continuously to inform its products on social media. Keywords: Brand image, Word of Mouth, Price, tourist decisions